2023
DOI: 10.1002/adma.202308502
|View full text |Cite
|
Sign up to set email alerts
|

A 2D Heterostructure‐Based Multifunctional Floating Gate Memory Device for Multimodal Reservoir Computing

Jiajia Zha,
Yunpeng Xia,
Shuhui Shi
et al.

Abstract: The demand for economical and efficient data processing has led to a surge of interest in neuromorphic computing based on emerging two‐dimensional (2D) materials in recent years. As a rising van der Waals (vdW) p‐type Weyl semiconductor with many intriguing properties, tellurium has been widely used in advanced electronics/optoelectronics. However, its application in floating gate memory devices for information processing has never been explored. Herein, we report an electronic/optoelectronic floating gate mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The 532 nm laser is often used to test the photoelectric properties of MoS 2 and has excellent light absorption intensity in the visible light band. 10,15,53 To assess the optical storage potential, applying a +60 V gate voltage for 10 ms (Fig. 4e) puts the device in HRS, then subjected the device to periodic light pulses using a 532 nm laser at an intensity of 27.5 mW cm −2 for 1 s with a 5 s interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 532 nm laser is often used to test the photoelectric properties of MoS 2 and has excellent light absorption intensity in the visible light band. 10,15,53 To assess the optical storage potential, applying a +60 V gate voltage for 10 ms (Fig. 4e) puts the device in HRS, then subjected the device to periodic light pulses using a 532 nm laser at an intensity of 27.5 mW cm −2 for 1 s with a 5 s interval.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 This has prompted the search for new memory technologies, like those utilizing ultrathin two-dimensional (2D) materials, including graphene, hexagonal boron nitride, and transition metal dichalcogenides (TMDs). 8–11 These materials, known for their unique layered structures and clean interfaces, form van der Waals (vdW) heterostructures, ideal for next-generation electronic and optoelectronic devices. 12–17 Memory devices employing 2D crystal floating gates have shown exceptional data retention and durability, despite variations in performance metrics such as on/off ratios and memory window sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 30,38 have demonstrated that direct tunneling is dominant at small gate voltages, whereas the Fowler− Nordheim (F−N) mechanism dominates the tunneling process under large gate voltages. The current equation for F−N tunneling can be expressed as 33 = * * i k j j j j j j j y…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3d shows an F−N plot of the I−V curve obtained from the tests, and the linear relationship between them indicates that the F−N tunneling mechanism dominates in our device. 30,38,40,41 Electrical and Optical Multilevel Storage. Our device has a high erasing/programming current ratio, which enables multilevel storage in a single memory cell.…”
Section: Resultsmentioning
confidence: 99%
“…By employing such materials including both organic and inorganic substances, the degree to which charge is trapped in the floating gate can be controlled based on the exposure to light. This capability opens up possibilities for devices such as optical memories, where both optical detection and memory operations can occur simultaneously, photonic logic circuits utilizing light as an input for logical operations, or photonic synapses where light serves as the stimulus for memory components.…”
mentioning
confidence: 99%